Improving Speaking Confidence in Elementary School Teacher Education Students through Video-Based Assignments - Dinda Tri Anggraini; Wiwin Rita Sari; Muhardila Fauziah; Sophie Nabila (Alifbata : Jurnal Pendidikan Dasar, 2026)
This study aims to determine the level of confidence of students of Universitas PGRI Yogyakarta in speaking by implementing a video-based assignment program. The research method is classroom action research with the Kurt Lewin model. The data source of this study is videos from 40 students of the Elementary School Teacher Education Study Program (PGSD) UPY uploaded to YouTube. The results of the study showed that before the action was carried out, students' speaking skills in linguistic and non-linguistic aspects were still inadequate, the data showed that 31% of 40 students achieved a passing grade. After cycle 1, the results were 60.6% and cycle 2 the results were 89.7%, there was a significant increase in students' confidence in speaking. So it can be concluded that the video-based assignment program carried out was declared valid, practical, and effective for use in the learning process and increasing students' confidence in speaking skills.